Association of TLR4 Gene Genotype and Resistance Against Salmonella enteritidis Natural Infection in Kampung Chicken - Ulupi , Niken; Muladno; Sumantri, Cece; Wibawan, I. Wayan Teguh (International Journal of Poultry Science, 2013)
Eggs of kampung chicken play an important role as substance in ‘jamu preparation’ in Indonesia, mostly provided and consumed without cooking. Salmonella free eggs become significant in producing the safe ‘jamu preparation’ and such eggs might be produced by chickens which have high resistancy to this bacteria. One of excellent markers showing resistance of chicken against Salmonella is an active Toll-like Receptor 4 (TLR4) gene. TLR4 is a phagocytes cell surface receptor that plays a role to recognize lipopolysaccaride (LPS) of gram negative bacteria including Salmonella enteritidis. It is transcribed by TLR4 gene and conserved in the activation of the non-specific immune system. The aim of the research was to prove how kampung chicken resistant against natural infection of S. enteritidis, using TLR4 gene as marker. TLR4 gene was genotyped in 50 kampung chickens with PCR-RFLP. Then biological assays of resistance indicator were measured. The genotyping result on exon 2 (220 bp in size) identified 3 genotypes of TLR4 gene in kampung chicken: AA, AG and GG. Concentration of leucocytes and their differentiation were not significantly different in AG and GG genotype. The value of it from AA genotype was similar to them. There was no S. enteritidis finding in blood and eggs produced by AA, AG, GG chickens. Specific IgY to S. enteritidis was positively found in kampung chickens serum and egg yolk. Concentration of specific IgY in kampung chicken egg yolk was found very high. The study postulated that most likely kampung chicken resistant to S. enteritidis natural infection.